The Female Word - Castillo Rodríguez, Larissa (2023)
Through erotic and intimate content poetry, the lyrical voice vindicates loneliness, productive leisure, beauty, and the fleetingness of the sexual-carnal encounter, as well as the persistence of contradiction, which is, after all, what makes us humans.